Determination Methodology of the Fiduciary Law and Critic Towards Sharia Fiduciary Institutional Dualism and its Legislation - Iwan Setiawan (International Journal of Nusantara Islam, 2014)
The Qur’an’s verse, Al-Baqarah: 283, explains rahn in a trip condition, however, the fact that the enforcement of rahn also occurs in muqim condition. Syar’ah fiduciary needs to be included into law as Muslims in Indonesia are the majority and based on the decision of OKI (Islamic Conference Organization), Indonesia is as an Islamic country. Therefore, by being supported by Pancasila, it generates God Sovereignty theory. The research method used is normative juridical method: that is the law research method done by researching literature. The research shows that: 1) the fiduciary truth (rahn) in Islamic law is (syara’) making a thing having value of property in the view of Syara’ as a debt guarantee, which enables to take the whole or part of the debt of the thing. Method of istinbath al-hukmi is related to the fiduciary done by the fiduciary institution using qiyas (metaphor), 2) the emergence of dualism of sharia fiduciary institution and sharia banking was caused by the existence of fatwa of National Sharia Board MUI (Indonesian Council of Religious Scholars) No: 25/DSN-MUI/lII/2002, and Fatwa of National Sharia Board MUI No: 26/DSN-MUI/II1/2002, in which sharia financial institution is allowed to produce the product which accords with syarih principles, 3) critic towards law No. 21, 2008 and governmental regulations No. 51, 2011 are not directly clarified, but has similarities and explanations concerning a product that must accord with sharia principles.